Strategi Komunikasi Program Kampung Iklim Dalam Mendorong Partisipasi Generasi Z Pada Kegiatan Sosial - Sarah Rizqi Aprilia; Iin Soraya; Yogi Ariska (Sinergi : Jurnal Ilmiah Multidisiplin, 2025)
The growing concern over climate change has prompted the Indonesian government to implement the community-based Climate Village Program (ProKlim). However, participation from Generation Z in this program remains relatively low, despite their significant potential as agents of change. This study aims to examine the communication strategies of ProKlim in encouraging Generation Z’s involvement in environmental social activities in RW 03, Cempaka Putih Timur. The research adopts a qualitative approach by applying the AIDDA communication model (Attention, Interest, Desire, Decision, Action) and Lasswell’s communication theory (Who Says What In Which Channel To Whom With What Effect). The findings show that the communication strategy comprehensively covers all elements of communication. Communicators employ both direct approaches and social media, delivering messages in a simple and easily understood manner. Although digital media utilization is not yet optimal, the approach has begun to attract the attention and interest of Generation Z and foster real actions. These findings indicate that the implemented communication strategy has the potential to significantly enhance Generation Z’s participation in future environmental sustainability efforts. Keywords: Communication Strategy, Climate Village Program, Generation Z, AIDDA Abstrak Perubahan Iklim yang kian mengkhawatirkan mendorong implementasi Program Kampung Iklim (ProKlim) berbasis komunitas oleh pemerintah Indonesia. Namun, partisipasi Generasi Z dalam program ini masih tergolong rendah, meskipun mereka memiliki potensi besar sebagai agen perubahan. Penelitian ini bertujuan untuk mengkaji strategi komunikasi ProKlim dalam mendorong keterlibatan Generasi Z pada kegiatan sosial lingkungan di RW 03 Kelurahan Cempaka Putih Timur. Penelitian menggunakan pendekatan kualitatif dengan menerapkan model komunikasi AIDDA (Attention, Interest, Desire, Decision, Action) dan unsur komunikasi Lasswell (Who Says What In Which Channel To Whom With What Effect). Hasil penelitian menunjukkan bahwa strategi komunikasi telah mencakup seluruh unsur komunikasi secara menyeluruh. Komunikator menggunakan pendekatan langsung dan media sosial dengan penyampaian pesan yang sederhana dan mudah dipahami. Meskipun pemanfaatan media digital belum maksimal, pendekatan ini mulai berhasil menarik perhatian dan minat Generasi Z serta mendorong tindakan nyata. Temuan ini mengindikasikan bahwa strategi komunikasi yang diterapkan berpotensi meningkatkan partisipasi Generasi Z secara lebih signifikan dalam upaya keberlanjutan lingkungan di masa depan. Kata Kunci: Strategi Komunikasi, Program Kampung Iklim, Generasi Z, AIDDA